Does kaolin clay really create a perfect hydraulic interface contact between materials?. (30th November 2020) - Vereecken, Evy; Schůtová, Petra; Roels, Staf
Highlights: Kaolin clay does not create a perfect hydraulic contact. High absorptive samples assembled with kaolin show an interface resistance (RIF ) in the order of 9 000 m/s and 25 000 m/s. For low absorptive samples, the interface resistance is negligible. The distance from contact interface to water plain influences the impact of the RIF in a free water uptake experiment. Abstract: In literature, kaolin clay is often put forward to create a perfect hydraulic contact across the interface of building materials. This paper studies, based on imbibition experiments, if kaolin clay truly nullifies a hydraulic interface resistance between materials. Thereto, a comparison is made between the water uptake by monolithic samples and by samples composed using kaolin clay. An interface resistance is observed and estimated to be in the order of 6 000 m/s to 12 000 m/s for a high absorptive brick and around 25 000 m/s for calcium silicate. For low absorptive materials or for an interface far from the water plain, a hydraulic interface resistance is probably also present. Though, in this case, the interface resistance is too low to have a noticeable impact on the cumulative inflow.